A numerical study of drag reduction performance of simplified shell surface microstructures. (1st December 2020) - Qiu, Hangyu; Chauhan, Kapil; Lei, Chengwang
Abstract: Antifouling and drag reduction are two critical issues for the shipping industry. Previous studies have revealed that biomimetic shell surfaces have distinct antifouling features. In this study, ten simplified surface microstructures with the same cross-section area are designed based on the antifouling scale of the shell surface morphology. Turbulent flow over the riblet structures is simulated using a finite volume based CFD solver with the Shear Stress Transport k-ω model to examine the effects of the riblet structures on skin friction with mean flow velocities ranging from 1 to 7 m/s. The corresponding dimensionless square root of the groove cross-section area is l g + ≈4.5–25.6. Considering the predicted drag performance and issues concerning riblet tip rounding and fabrication, an optimal geometry with both antifouling and drag reduction features has been identified. The present study confirms that the riblets lift off streamwise vortices, pushing the high turbulent kinetic energy region away from the surface, and impede the spanwise movement of streamwise vortices, leading to skin-friction reduction. Further, the investigation of the effect of the riblet interval on the drag behaviour indicates the existence of a balance point between the wetted perimeter and the total area of the riblet surface for minimizing drag. Highlights: Drag performance of antifouling surfaces are investigated numerically. Three shapes of riblets with various configurations are examined. A specific riblet design with a circular cross-section has both antifouling and drag reduction potentials. For a given cross-section area of riblets, a correlation between drag reduction and wetted perimeter is identified. A simplified drag reduction mechanism is proposed.